The Mechanism of Non-Financial Firms’ Performance and Corporate Governance Leadership - Huda Alsayed (Business Ethics and Leadership)
This paper investigates the non-financial listed companies in the Kingdom of Saudia Arabia. The model was built based on previous theories like agency and stewardship theories. To fulfill the objective of this study, a cross-sectional regression method was applied, and two measures of financial performance, Tobin Q and Return on Assets, were used to assess five corporate governance practices. The empirical test was conducted on 114 listed firms between 2010‒2020. The Stata program was used to analyze the hypotheses. The companies in the sample are from various industries, making outcomes more diverse. The results indicate that insider ownership and board size significantly influence return on assets. Conversely, CEO duality, firm size, and leverage are statistically significant factors that affect Tobin’s Q. These findings were validated through a check for heteroscedasticity. Additionally, the fluctuations in the results may be attributed to the distinction between effects and causes. Another primary reason is that family companies are among the most common firms in Islamic countries. This dramatically impacts the traits of board members and, by extension, the corporate governance system. The results also show that businesses Islamic nations are less willing to take risks than they are. In addition, the study provides recommendations on how to improve a company’s financial performance using appropriate corporate governance structures. Moreover, it can be useful for researchers and policymakers for improving the performance of companies through the implementation of an improved system of corporate governance practices.